Awal Penyebaran dan Perkembangan Agama Islam di Pulau Bali - Rinaldi Permana Putra (Jurnal Keislaman, 2023)
Bali is an archipelago in Indonesia which is known as the Island of the Gods and the Island of a Thousand Temples, because of the very strong Hindu culture in every social structure. So, it seems like there is no other religion besides Hinduism. However, in reality it turns out that not all people adhere to Hinduism. Many of them even adhere to Islam. In fact, the coming of Islam to Bali also coincided with the triumph of Hinduism in Bali in the 15th century. This research aims to find out how Islam developed and spread on the island of Bali and to find out how tolerance was created between Hindus and Muslims in Bali. The method used in this research is qualitative research with a historical approach. From this research it can be concluded that Islam spread peacefully and steadily since the 15th century during the Gelgel Kingdom. Then a few years later, there were many immigrants from Javanese, Madurese, Sasak, Chinese, Arabs and others who made other communities wider. As for the life between Hindus and Muslims in Bali and other people walk side by side, harmonious, and rich in good and strong tolerance.